2019
DOI: 10.3390/cryst9110558
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrical Properties of Na0.5Bi0.5TiO3 Epitaxial Films with (110) Orientation

Abstract: Pt/Na 0.5 Bi 0.5 TiO 3 /La 0.5 Sr 0.5 CoO 3 (Pt/NBT/LSCO) ferroelectric capacitors were fabricated on (110) SrTiO 3 substrate. Both NBT and LSCO films were epitaxially grown on the (110) SrTiO 3 substrate. It was found that the leakage current density of the Pt/NBT/LSCO capacitor is favorable to ohmic conduction behavior when the applied electric fields are lower than 60 kV/cm, and bulk-limited space charge-limited conduction takes place when the applied electric fields are higher than 60 kV/cm. The Pt/NBT/LSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…The 600 1C (the lowest growth temperature in this work) films show the highest ON/OFF ratio with the best device uniformity. The minimum growth temperature of 600 1C that we tried in our work is within the optimum growth temperature (600-650 1C) reported in many works for PLD growth of NBT films 48,61,62 (although one study reported a substrate temperature of 550 1C, where they used a lower oxygen pressure during deposition 36 ).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The 600 1C (the lowest growth temperature in this work) films show the highest ON/OFF ratio with the best device uniformity. The minimum growth temperature of 600 1C that we tried in our work is within the optimum growth temperature (600-650 1C) reported in many works for PLD growth of NBT films 48,61,62 (although one study reported a substrate temperature of 550 1C, where they used a lower oxygen pressure during deposition 36 ).…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, NBT has potential industrial interest as it can be sputtered at relatively low temperatures. 36 However, while a report in NBT has shown ferroelectric-polarization-controlled RS with 10 3 ON/OFF ratio, 45 V o controlled RS has not been demonstrated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been known that the pure NBT ceramics have a square‐shape P‐E hysteresis loop [ 131 ] with P max ≈ 38 μC cm −2 , which can be doubled when grown into thin films. [ 142 ] By means of chemical modification, for example, dilute Mn doping, Yang et al., reported that the P max and E B can be increased to 113 μC cm −2 and 2.3 MV cm −1 in Mn:NBT‐BT‐BiFeO 3 (Mn:NBT‐BT‐BFO) thin films. [ 143 ] This gives rise to a very high recoverable energy density ( U e = 81.9 J cm −3 ) with η at a value of 64.4%.…”
Section: Electrostatic Energy Storage Systemsmentioning
confidence: 99%
“…Two papers are dedicated to thin-film capacitor applications. The results on structure and electrical properties of lead-free Na 0.5 Bi 0.5 TiO 3 based epitaxial films are reported by Song et al [6]. Pt/Na 0.5 Bi 0.5 TiO 3 /La 0.5 Sr 0.5 CoO 3 (Pt/NBT/LSCO) was fabricated on a (110) SrTiO 3 substrate.…”
mentioning
confidence: 69%